THE STANDARDS OF MEDICAL CARE WITH SELF CARE FOR DIABETES MELLITUS OUTPATIENTS - Wirawan, Handi; Soewondo, Prastuti (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Diabetes mellitus (DM) is a chronic disease that will be carried for life. DM management requires the participation of doctors, nurses, nutritionists, and other health workers. Based on this, Diabetes mellitus (DM) requires awareness, self care and collaboration from all health workers. The awareness, self care and collaboration of health workers on the importance of carrying out two-way services in patients with diabetes mellitus are the supporting forces in the DM case control program according to the standard of medical care. This study is to find out the standard of medical care with self care for diabetes mellitus outpatients. Methods: A systematic review through an article review to find out the standard of medical care with self care for diabetes mellitus outpatients. The inclusion criteria for the articles used were diabetes mellitus outpatients self care, while the exclusion criteria were abstract articles, articles that did not use English and the non full text articles. Article search is limited to articles in English accessed from internet searches from databases, namely: NCBI and Knowledge E with the keyword standard medical care, self care, and diabetes mellitus. Results: Based on the 7 articles with the same title, the screening was carried out according to the criteria for inclusion and exclusion, obtained 5 articles for further review. Self care in diabetes is a series of skills that are very important to improve the effectiveness of self management in diabetes awareness of the patient itself and collaboration with health workers. Nurses deal with collaborative problems both between health workers and patients by using doctor's provisions and prescribed interventions, to minimize complications from the occurrence. Conclusion: One of the most factor that need to be improved to decreased the case of DM is how to maintain the self care of DM outpatients. It is very important because the self care is helping the outpatient with DM to maintain their own health. Because of that, the important recommendation for DM outpatient is to maintain and increasing their standard of medical care with self care.